(untitled) (KYAMC Journal, 2017)
Background: The cerebellum is a very important part of central nervous system. It is involved in the maintenance of balance and posture, coordination of voluntary movements, motor learning and cognitive functions such as language. Inferior cerebellar peduncle connects the spinal cord and medulla oblongata with the cerebellum and carries unconsciousness proprioceptive information from body and limb. The mean diameter of inferior cerebellar peduncle at birth is only a fraction of the adult diameter then diameter increases up to certain age and decreases in old age. Objectives: The present study was done to observe the diameter of the inferior cerebellar peduncle in different age groups of Bangladeshi cadaver which will serve as a baseline data for clinician about the neurological disorders in our country. Materials and Methods: A cross sectional, analytical type of study was carried out in the department of anatomy, Mymensingh Medical College, Mymensingh from April’2009 to September’2009. A total of 63 cerebellums were collected of which 40 (male 25 and female 15) were from during postmortem of unclaimed Bangladeshi cadaver aged between 5 to 60 years and 23 (male 14 and female 9) were from caesarian section of dead fetuses aged between 34 wks to 42 wks. of gestation. The collected sample was grouped into three age groups like Group A (34 to 42 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years). The diameters of the inferior cerebellar peduncles were measured by using slide calipers and expressed in millimeter (mm). Result: The mean (±SD) diameter of right inferior cerebellar peduncle was in Group A 5.40±1.13, B 7.72±1.18 and C 6.77±1.68 mm respectively and the mean (±SD) diameter of left inferior cerebellar peduncle was in Group A 5.20±1.09, B 7.59±1.23 and C 6.66±1.58 mm respectively. Conclusion: From the present study it is observed that the mean diameter of the inferior cerebellar peduncle increased with age upto certain level then slightly decreased in the late age. The result of the present study will enrich the information pool on diameter of the inferior cerebellar peduncle of Bangladeshi people. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 27-32